Exome sequence analysis in consanguineous Pakistani families inheriting Bardet‐Biedle syndrome determined founder effect of mutation c.299delC (p.Ser100Leufs*24) in BBS9 gene. Issue 8 (11th July 2019) - Muzammal, Muhammad; Zubair, Muhammad; Bierbaumer, Sophie; Blatterer, Jasmin; Graf, Ricarda; Gul, Aisha; Abbas, Safdar; Badar, Muhammad; Abbasi, Ansar Ahmad; Khan, Muzammil Ahmad; Windpassinger, Christian
Abstract: Background: Bardet‐Biedl syndrome (BBS) is characterized by a heterogeneous phenotypic spectrum of retinopathy, intellectual disability (ID), obesity, polydactyly, and kidney dysfunctions as the major clinical features. Genetic investigations have reported 21 BBS genes, the products of which are mostly located at the centrosome, basal body or the ciliary transition zone. Methods: In the present genetic report, we analyzed two apparently unrelated consanguineous BBS families from Dera Ismail Khan (D.I.Khan) district, Pakistan. Genetic mapping was performed using Whole exome sequencing and Sanger sequencing. Results: Whole exome sequencing identified a recently reported single base deletion NM_001033604.1:c.299delC in the fourth exon of BBS9 in both families. The identified frameshift mutation is predicted to cause premature truncation of the expressed protein (p.Ser100Leufs*24). This mutation has previously been mapped in a consanguineous Pakistani family; therefore this is the second report of this particular mutation in two additional BBS families originating from different locations. Conclusion: We speculate the evolutionary significance of this mutation and assume its strong founder effect in the Khaisoori tribe of D.I.Khan. Based on these findings, we suggest developing a molecular diagnostic test that may be used for premarital and prenatal screening of families at risk of BBS. Abstract : This study describes the molecular characterization of two consanguineous Pakistani families presenting with BBS syndrome. Using whole exome sequencing, we were able to map deletion mutations in BBS9. The study helped us to explore the founder effect of this mutation in Pakistani families.